An assessment of the economic impact of drip irrigation in vegetable production in India - A Narayanamoorthy; M Bhattarai; P Jothi (Agricultural Economics Research Review, 2023)
Several studies have assessed the technical and economic feasibility of drip irrigation in a number of crops and have proven its potential to save water and energy, and to increase crop yields. However, only a few studies have assessed its techno-economic potential in vegetable crops. In this paper, using survey data from Indian state of Tamil Nadu, we assess its potential in brinjal, a widely cultivated and consumed vegetable in the country. The findings indicate that besides savings in water (40%) and electricity (629 kwh/acre), the drip irrigation reduces use of other inputs, e.g. fertilizers (31%), and enhances crop yield by 52%. On the whole, its application in brinjal results in 54% higher net returns over the conventional method of irrigation. Benefit-cost ratio in drip irrigation is quite attractive making it a viable option for sustainable management of irrigation water.